The Nightingalean theory and its legacy in the prevention of surgical infections in Brazil: testing technology (Research, Society and Development, 2021)
The objective of this article is to reflect on the contributions of the legacy left by Florence Nightingale, through his environmental theory, discussing conceptual, theoretical, and practical approaches to the policies for the prevention and control of surgical infections in Brazil and the empowerment of Nurses, through testing environment disinfection technology. Method: it is a theoretical reflection, based on bibliographic research for theoretical foundation, with a qualitative approach. Result: the environmental theory developed by Florence Nightingale has been widely used by health care establishments from ancient times to the present day. The nurse has the full capacity to carry out testing with technologies. However, they need to be trained and immerse themselves in the area of the research, in addition to committing themselves to develop all the stages involved in the study rigorously. Still, they also need to have financial resources, which need to be injected into public universities, institutions, and research institutes, aimed at scientific research in Brazil. Conclusion: Florence Nightingale remains present with her precious teachings for Nurses and other health professionals and other areas. Her contributions are in line with the prevention and control of healthcare infections, especially surgical infections. In the meantime, the nurse is a fundamental part of the care capable of testing a disinfection technology in the surgical environment based on ultraviolet C-radiation.